Pemberdayaan Masyarakat Tani Desa Kayuuwi Kecamatan Kawangkoan Tentang Pembuatan Pupuk Organik dari Limbah Pertanian dan Rumah Tangga : Community Empowerment of Kayuuwi Village Farmers, Kawangkoan District Regarding Organic Fertilizer Based on Agricultural and Household Waste - Satiman, Utari; Rungkat, Jouveline; Batmetan, Johan; Taulu, Marthy (Sam Ratulangi University, 2025)
The Community Service activity partners are the Farmer Community, who are members of the Berkat Kayuuwi Kawangkoan Minahasa farmer group, with the following problems faced by the partners: 1) Low knowledge of farmer group members about organic fertiliser. 2) Low skills of farmers in empowering agricultural waste and household waste into organic fertiliser. 3). Low knowledge and skills of farmers in innovating daily community life activities in Kayuuwi Village, Kawangkoan District, such as household activities, farming, livestock raising which are found to have much waste that can be used as raw materials for making organic fertiliser so that it can increase community income while improving the quality of the soil and the surrounding environment. The methods used to achieve the PKM objectives were carried out in stages and systematically, starting with outreach and training. Then, direct field assistance until all activities were completed and partner issues were resolved. In addition to theoretical training, participants were also involved in hands-on practice in making solid compost. They were taught how to use a simple shredder as part of the application of appropriate technology. Evaluation was conducted by comparing pre-test and post-test results to assess participants' knowledge gains. The evaluation results showed a significant increase in farmers' understanding and skills, even reaching a 300% increase in some topics. Furthermore, organic fertiliser produced from agricultural and household waste was also directly utilised in peanut cultivation activities by farmer groups. This activity was not only educational but also productive because it encouraged farmers to be independent in meeting their fertiliser needs and opened up small business opportunities in organic farming. ABSTRAK Mitra kegiatan Pengabdian Kepada Masyarakat (PKM) adalah Masyarakat Tani yang tergabung dalam kelompok tani Berkat Kayuuwi Kawangkoan Minahasa dengan permasalahan yang dihadapi mitra sebagai berikut: 1). Rendahnya pengetahuan anggota kelompok tani tentang pupuk organik. 2). Rendahnya keterampilan petani dalam memberdayakan limbah pertanian dan limbah rumah tangga menjadi pupuk organik. 3). Rendahnya pengetahuan dan keterampilan petani dalam menginovasi aktifitas kehidupan masyarakat sehari-hari di Desa kayuuwi Kecamatan Kawangkoan, seperti aktivitas Rumah tangga, bercocok tanam, beternak yang didapati banyak limbahnya yang bisa dimanfaatkan menjadi bahan baku pembuatan pupuk organik sehingga bisa menambah pendapatan masyarakat sekaligus memperbaiki kualitas tanah dan lingkungan sekitar. Metode yang digunakan untuk mencapai tujuan PKM dilakukan secara bertahap dan sistematis dimulai dari sosialisasi, pelatihan, hingga pendampingan langsung di lapangan sampai seluruh kegiatan selesai dan permasalahan mitra teratasi. Selain pelatihan teori, peserta juga dilibatkan dalam praktek langsung pembuatan pupuk kompos padat. Mereka diajarkan menggunakan mesin pencacah sederhana sebagai bagian dari penerapan teknologi tepat guna. Evaluasi dilakukan dengan membandingkan hasil pre-test dan post-test untuk menilai peningkatan pengetahuan peserta. Hasil evaluasi menunjukkan adanya peningkatan signifikan dalam pemahaman dan keterampilan petani, bahkan pada beberapa topik mencapai kenaikan hingga 300%. Tidak hanya itu, pupuk organik yang dihasilkan dari limbah pertanian dan rumah tangga juga langsung dimanfaatkan dalam kegiatan budidaya kacang tanah oleh kelompok tani. Kegiatan ini tidak hanya bersifat edukatif tetapi juga produktif karena mampu mendorong petani untuk mandiri dalam memenuhi kebutuhan pupuk serta membuka peluang usaha kecil di bidang pertanian organik.